(3GdJagje dChGFd UfGYg GdJfLjes - (3eMeO Hf CMeO, CHh GdQjMGf GdHjQhfj GdNhGQRej,J (B440 (3g` s
(3ChdgG (B:s
(3WhdkG cGf GdeYJQV Ydjg YQVkG hGdeYJQV Ydi cdjgeG YebkG hLQi GdQSe ai JSejI CWhd GdChd WhdkG hCbUQgeG YQVkG s
(3BNQgG (B:s
(3abO LgdgG GdefJSHhf EdjgG aVdkG Yf GdefJajf YfgG hGddg GdeSJYGf s
(3ajgG cKjQ ef GdLOGhd GdQShes
(3cJH Ydi GdUaMI GdChdi HNW MOjK GdbGfhf ddeSYhOi hgh ZdWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B314 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B205s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B22 s
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdadcs